Gambaran Darah Ikan Paweh (Osteochilus hasselti C.V.) dari Danau Lubuk Siam, Kecamatan Siak Hulu, Kabupaten Kampar - Titrawani Titrawani; Windarti Windarti; Vera Anggraini (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
The study on the haematological condition of Osteochilus hasselti C.V. has been conducted on January to February 2011 and aims to understand the blood parameter values of O.hasselti living in the healthy area.Fish samples were obtained from the Lubuk Siam dam that has good water quality.There were 30 fishes (15 males and 15 females), ranged from 9.5 to 14.5 cm SL.The blood was taken from the caudal vena using 1 ml syringe wet with 10% EDTA.Haematological parameters measured were haematocrit and leucocrit levels (Anderson and Siwicki, 1994), total erythrocyte and leukocyte (Schaperclaus, 1992).Results shown that the haematocrit and leucocrit level were 17–33.33 % and 1.72 - 3.12 % respectively. Total erythrocyte was 98,000 - 3,330,000 cells/mm3, total leukocytewas 125,000 - 333,000 cells/mm3.